Integral global sliding mode guidance for impact angle control - He, Shaoming; Lin, Defu; Wang, Jiang (IEEE, 2018)
This Correspondence proposes a new guidance law based on integral sliding mode control (ISMC) technique for maneuvering target interception with impact angle constraint. A time-varying function weighted line-of-sight (LOS) error dynamics, representing the nominal guidance performance, is introduced first. The proposed guidance law is derived by utilizing ISMC to follow the desired error dynamics. The convergence of the guidance law developed is supported by Lyapunov stability. Simulations with extensive comparisons explicitly demonstrate the effectiveness of the proposed approach.
Keywords: Aerodynamics; Convergence; Missiles; Closed-form solutions; Kinematics; Mathematical model